Bodies and Souls: Continuing Conundrums - Rambo, Lewis (The international journal for the psychology of religion, 1998)
Although affirming much of what Malony states, issue is taken with his treatment of sexuality. Sexuality has been a prime issue for Christianity and should be accorded a central focus in understanding body/soul problems. More attention should be paid to the natural sciences than Malony accepts. Further, there is no need to polarize imma- nence and transcendence in understanding religion, as Malony suggests.